Symptom Clustering in Older Taiwanese Children With Cancer - Yeh, Chao-Hsing; Chiang, Yi-Chien; Chien, Lung-Chang; Lin, Lin; Yang, Chao-Ping; Chuang, Huo-Li (Oncology nursing forum, 2008)
To derive symptom clusters occurring in a large group of older pediatric patients with cancer in Taiwan and to examine whether each cluster differed based on gender, type of cancer and disease, pain, and functional status. Descriptive, correlational study. Pediatric oncology inpatient unit and outpatient clinics in Taiwan. 144 pediatric patients with cancer, aged 10-18 years. Subjects completed the Memorial Symptom Assessment Scale 10-18, the Play Performance Scale for Children, and a demographic questionnaire. Medical records provided disease and treatment data. Cluster analysis techniques were used to identify the symptoms that clustered together by demographic characteristics, as well as disease, pain, and functional status. Symptom cluster, pain status, and functional status. Five clusters were identified from the statistical analysis. The symptoms that clustered together were somewhat surprising, and some can be explained by cultural differences. Patients with pain reported statistically significant higher distress in all five clusters. Five symptom clusters are identified in older Taiwanese children with cancer. The way and possible rationale of how these symptoms clustered together is discussed. This is the first study that used a statistical procedure to derive symptom clusters experienced by pediatric oncology patients. Knowledge from this study can provide a starting point to investigate the stability of symptom clusters with different states of disease, different populations, and over various periods of time.